Mutations identified in engineered Escherichia coli with a reduced genome - Kotaka, Yuto; Hashimoto, Masayuki; Lee, Ken-ichi; Kato, Jun-ichi (Frontiers in Microbiology, 2023)
Characterizing genes that regulate cell growth and survival in model organisms is important for understanding higher organisms. Construction of strains harboring large deletions in the genome can provide insights into the genetic basis of cell growth compared with only studying wild-type strains. We have constructed a series of genome-reduced strains with deletions spanning approximately 38.9% of the E. coli chromosome. Strains were constructed by combining large deletions in chromosomal regions encoding nonessential gene groups. We also isolated strains 33b and 37c, whose growth was partially restored by adaptive laboratory evolution (ALE). Genome sequencing of nine strains, including those selected following ALE, identified the presence of several Single Nucleotide Variants (SNVs), insertions, deletions, and inversions. In addition to multiple SNVs, two insertions were identified in ALE strain 33b. The first was an insertion at the promoter region of pntA, which increased cognate gene expression. The second was an insertion sequence (IS) present in sibE, encoding the antitoxin in a toxin-antitoxin system, which decreased expression of sibE. 5 strains of 37c independently isolated following ALE harboring multiple SNVs and genetic rearrangements. Interestingly, a SNV was identified in the promoter region of hcaT in all five strains, which increased hcaT expression and, we predict, rescued the attenuated 37b growth. Experiments using defined deletion mutants suggested that hcaT encodes a 3-phenylpropionate transporter protein and is involved in survival during stationary phase under oxidative stress. This study is the first to document accumulation of mutations during construction of genome-reduced strains. Furthermore, isolation and analysis of strains derived from ALE in which the growth defect mediated by large chromosomal deletions was rescued identified novel genes involved in cell survival.